2018
DOI: 10.1016/j.celrep.2018.10.068
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock Regulation of Hepatic Lipid Metabolism by Modulation of m6A mRNA Methylation

Abstract: SUMMARY Transcriptional regulation of circadian rhythms is essential for lipid metabolic homeostasis, disruptions of which can lead to metabolic diseases. Whether N6-methyladenosine (m6A) mRNA methylation impacts circadian regulation of lipid metabolism is unclear. Here, we show m6A mRNA methylation oscillations in murine liver depend upon a functional circadian clock. Hepatic deletion of Bmal1 increases m6A mRNA methylation, particularly of PPaRα. Inhibition of m6A methylation via knockdown of m6A methyltrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
169
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(188 citation statements)
references
References 59 publications
9
169
0
Order By: Relevance
“…Circadian disruption induces leptin resistance in mice, which may lead to obesity or metabolic syndromes, indicating different impacts of food intake in the liver depending on the timing of intake . A previous study has demonstrated that Alb ‐Cre‐mediated liver‐specific BMAL1 knockout mice have elevated mRNA methylation especially in peroxisome proliferator‐activated receptor alpha (PPARα) in the liver . PPARα promotes β‐oxidation of FFAs and lipid metabolism, and methylation of PPARα mRNA causes mRNA degradation and inhibition of PPARα expression leading to accumulation of triglycerides in the liver .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
“…Circadian disruption induces leptin resistance in mice, which may lead to obesity or metabolic syndromes, indicating different impacts of food intake in the liver depending on the timing of intake . A previous study has demonstrated that Alb ‐Cre‐mediated liver‐specific BMAL1 knockout mice have elevated mRNA methylation especially in peroxisome proliferator‐activated receptor alpha (PPARα) in the liver . PPARα promotes β‐oxidation of FFAs and lipid metabolism, and methylation of PPARα mRNA causes mRNA degradation and inhibition of PPARα expression leading to accumulation of triglycerides in the liver .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
“…[104][105][106] Studies in genetic mouse models that lack a functional clock due to a whole-body or tissue-specific knockout of essential core clock components reveal that a proper circadian oscillator function is indispensable for glucose, lipid and protein metabolism. 123 This finding further emphasizes that m6A RNA methylation plays an important regulatory role for the circadian modulation of metabolic outputs, via alteration of gene transcription and lipid metabolism. 31,59,71,77,[107][108][109][110][111] The nuclear receptor REV-ERBα is a key regulator of lipid, carbohydrate and protein metabolism.…”
Section: Of Mammalian Physiology and Metabolismmentioning
confidence: 84%
“…METTL3 conducted in vitro reduced PPARα methylation and increased its mRNA stability, thus leading to the altered hepatic accumulation of lipids. 123 This finding further emphasizes that m6A RNA methylation plays an important regulatory role for the circadian modulation of metabolic outputs, via alteration of gene transcription and lipid metabolism. 124 CRY1 and CRY2 proteins reduce fasting glucose production by inhibiting glucagon-induced DIBNER liver gluconeogenesis.…”
Section: Dibnermentioning
confidence: 84%
“…In contrast, NV was effective at highlighting individual cells that were markedly different numerically in mRNA from their neighbours. NV is therefore a relevant measure for questions where the absolute RNA number is important, for example when a threshold expression level is required for a particular process to occur 29,30 , or post-transcriptional buffering mechanisms that maintain constant mRNA levels 31,32 . PV also effectively highlighted individual cells that differed from their neighbours, but in proportional expression rather than actual.…”
Section: Discussionmentioning
confidence: 99%